2020
DOI: 10.1002/ejhf.2064
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics of patients with heart failure with preserved ejection fraction in the EMPEROR‐Preserved trial

Abstract: Aims EMPEROR‐Preserved is an ongoing trial evaluating the effect of empagliflozin in patients with heart failure with preserved ejection fraction (HFpEF). This report describes the baseline characteristics of the EMPEROR‐Preserved cohort and compares them with patients enrolled in prior HFpEF trials. Methods and results EMPEROR‐Preserved is a phase III randomized, international, double‐blind, parallel‐group, placebo‐controlled trial in which 5988 symptomatic HFpEF patients [left ventricular ejection fraction (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 26 publications
5
72
0
2
Order By: Relevance
“…Empagliflozin significantly improves cardiovascular and renal outcomes in patients independent of baseline diabetes status in the EMOEROR-Reduced trial (Packer et al, 2020) and significantly improves cardiac function and quality of life in HFrEF patients in the EMPA-TROPISM trial (Santos-Gallego et al, 2021). The clinical trial to investigate the effects of SGLT2i on HFpEF is still in progress (Anker et al, 2020).…”
Section: Sglt2 Inhibitors Can Increase the Production Of β-Ohbmentioning
confidence: 99%
“…Empagliflozin significantly improves cardiovascular and renal outcomes in patients independent of baseline diabetes status in the EMOEROR-Reduced trial (Packer et al, 2020) and significantly improves cardiac function and quality of life in HFrEF patients in the EMPA-TROPISM trial (Santos-Gallego et al, 2021). The clinical trial to investigate the effects of SGLT2i on HFpEF is still in progress (Anker et al, 2020).…”
Section: Sglt2 Inhibitors Can Increase the Production Of β-Ohbmentioning
confidence: 99%
“…There are 2 ongoing trials which designed to investigate the clinical effect of SGLT2i in HFpEF patients. The EMPEROR-Preserved trial enrolled 4,126 HFpEF patients to empagliflozin or placebo ( NCT03057951 ), 35) 36) and the DELIVER trial enrolled 4,700 patients to dapagliflozin or placebo ( NCT01297257 ); both clinical trials are expected to be completed and reported in 2021–2022.…”
Section: Effects On Heat Failure Events In Patients With Heat Failure With Preserved Ejection Fractionmentioning
confidence: 99%
“…Recently in this Journal Anker et al published the trial design and baseline characteristics of the EMPEROR-Preserved trial. 1,2 Compared to previous heart failure with preserved ejection fraction (HFpEF) trials investigating established drugs for the treatment of heart failure with reduced ejection fraction (HFrEF), the mechanistic evidence of empagliflozin as a rationale for treating patients with HFpEF seems to be more promising. Accordingly, we believe that the first experimental findings in human HFrEF and HFpEF myocardium have to be taken into consideration in this elegant clinical trial as they pave the way for a deeper mechanistic understanding of the potential effects of empagliflozin in the EMPEROR-Preserved trial.…”
Section: A Mechanistic Rationale For the Investigation Of Sodium-glucose Co-transporter 2 Inhibitors In Heart Failure With Preserved Ejecmentioning
confidence: 99%